2020
DOI: 10.1186/s12860-020-0249-5
|View full text |Cite
|
Sign up to set email alerts
|

A doublecortin-domain protein of Toxoplasma and its orthologues bind to and modify the structure and organization of tubulin polymers

Abstract: Background: TgDCX is a doublecortin-domain protein associated with the conoid fibers, a set of strongly curved non-tubular tubulin-polymers in Toxoplasma. TgDCX deletion impairs conoid structure and parasite invasion. TgDCX contains two tubulin-binding domains: a partial P25α and the DCX/doublecortin domain. Orthologues are found in apicomplexans and their free-living relatives Chromera and Vitrella. Results: We report that isolated TgDCX-containing conoid fibers retain their pronounced curvature, but loss of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 63 publications
3
30
0
Order By: Relevance
“…Indeed, even in Toxoplasma the function of the conoid is relatively poorly understood. Most studies of individual protein elements have identified molecules required for its assembly and stability [29,[31][32][33][34][35]. But other studies have implicated roles in control processes, including activating motility and exocytosis, both of which are requirements for invasion as well as host egress events [24,28,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, even in Toxoplasma the function of the conoid is relatively poorly understood. Most studies of individual protein elements have identified molecules required for its assembly and stability [29,[31][32][33][34][35]. But other studies have implicated roles in control processes, including activating motility and exocytosis, both of which are requirements for invasion as well as host egress events [24,28,30].…”
Section: Discussionmentioning
confidence: 99%
“…The other is that we still know relatively little of the molecular composition of the conoid that would allow the objective testing for the presence of a homologous structure [5]. The conspicuous ultrastructure of conoids such as those of coccidians draw attention to tubulin being a major element, however it is known that there are other conoid proteins responsible for its assembly, stability, and function during invasion [24,[28][29][30][31][32][33][34][35]. To test if a homologous conoid cell feature is present in Aconoidasida, but cryptic by traditional microscopy techniques, fuller knowledge of the molecules that characterise this feature in a 'classic' conoid model is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid sequences needed for tubulin/microtubule binding located in the C-terminus of long-type TPPPs can be found in another TPPP-like protein, apicortin, occurring mostly in apicomplexan parasites [ 21 ]. Indeed, the necessity of this protein for the formation of the structure of the conoid, the nontubular polymeric form of tubulin, was proven [ 22 ]. Since the “truncated” TPPP lacks these amino acids thus it is a logical conclusion that it very probably is not able to bind microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…This domain is also known to play a role in the stabilization of microtubules [ 25 , 26 ]. The two domains, the partial p25alpha and the DCX, have some homology: 22% identity and 30% similarity [ 28 ].…”
Section: Domainsmentioning
confidence: 99%
“…Otherwise, the sequences are very similar, independently of whether the protein can be found in an apicomplexan species or not. It was shown by Leung et al [ 28 ] that this region of the protein has an outstanding role in tubulin binding.…”
Section: Primary Secondary and Tertiary Structurementioning
confidence: 99%